Strategi Pendidikan dan Pembelajaran Berbasis Kolaborasi Dalam Pendidikan Agama Islam - M. Umar Mahmudi; Muhammad Rifa’i Subhi (https://ejournal.insuriponorogo.ac.id/, 2023)
Collaborative learning has become an attractive approach in education, including in Islamic Religious Education (PAI). This article discusses the meaning, concept and implementation of collaboration-based learning in PAI. Collaborative learning is a group learning strategy where students work together in constructing their knowledge. This article explains the steps in collaboration-based learning, including student orientation, group formation, assignment preparation, and facilitation of the collaboration process. Apart from that, this article also discusses the benefits of collaboration-based learning, such as developing social skills, a sense of responsibility, and high learning motivation. However, there are also challenges in its implementation, such as teacher skills required in group management and evaluating learning outcomes. The objectives of this research article include; 1). To analyze the definition of collaborative learning strategies, 2). To analyze the concept of collaborative learning, 3) To analyze the implementation of collaboration-based Islamic Religious Education, and 4) To analyze the advantages and disadvantages of collaboration-based Islamic Religious Education learning. This research article uses a qualitative approach. Data collection techniques use observation, interviews and documentation. In addition, data collection was carried out using the document study method using an instrument format for identifying discussion elements. Data was analyzed descriptively, quantitatively and qualitatively. The research results show that collaborative learning in PAI subjects is useful for helping students build understanding. Through this learning, students can also provide assistance to each other through intellectual guidance which enables them to work on more complex tasks. Of course, this will be difficult to achieve if done individually.